2021
DOI: 10.1159/000516097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute Central Serous Chorioretinopathy Using Enhanced Depth Imaging Optical Coherence Tomography and Multifocal Electroretinography

Abstract: mfERG; multifocal electroretinography, *Mann-Whitney U test Table 4. Pearson's correlation analyses between amplitude of multifocal electroretinography, bestcorrected visual acuity, and retinal thickness Ring 4 462.39 ± 87.06 452.48 ± 103.95 0.551 Ring 4 Ring 5 477.08 ± 94.15 468.76 ± 125.67 0.817 Ring 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previously, we evaluated patients with acute phase CSC using enhanced depth imaging – OCT and mfERG [17]. In this study, we found that the retinal response from mfERG was impaired in the area beyond the SRD, and the degree of SRF was not associated with mfERG dysfunction; only subfoveal choroidal thickness was associated with mfERG dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…Previously, we evaluated patients with acute phase CSC using enhanced depth imaging – OCT and mfERG [17]. In this study, we found that the retinal response from mfERG was impaired in the area beyond the SRD, and the degree of SRF was not associated with mfERG dysfunction; only subfoveal choroidal thickness was associated with mfERG dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…When it comes to visual function loss, the mechanisms differ between acute and chronic CSC. In acute CSC, due to the retinal layer morphology being largely intact, visual function impairment is caused by the accumulation of SRF [ 4 , 5 , 7 , 23 ]. In contrast, in chronic CSC, visual function loss predominantly arises due to the disruption of the outer retinal layers and RPE [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the findings of a study that showed mfERG impairment within the area of SRF accumulation [ 5 ]. Conversely, several studies have also indicated that mfERG measurements are affected beyond the area of SRF [ 23 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%